2020
DOI: 10.1097/tp.0000000000003070
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation in Patients Older Than 60 Years With High Comorbidity. Is There a Survival Benefit? A Multicenter Study in Argentina

Abstract: Background. The impact of renal transplantation (RT) in the elderly with many comorbid conditions is a matter of concern. The aim of our study was to assess the impact of RT on the survival of patients older than 60 years compared with those remaining on the waiting list (WL) according to their comorbidities. Methods. In this multicentric observational retrospective cohort study, we included all patients older than 60 years old admitted on the WL from 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…We identified 48 studies eligible for this systematic review. 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 After data extraction and further screening, we found 18 studies containing sufficient non-overlapping outcome data suitable for meta-analysis. 24 27 30 31 32 33 34 36 42 48 50 52 61 62 64 66 67 68 Figure 1 shows a PRISMA flow diagram detailing the process of study selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 48 studies eligible for this systematic review. 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 After data extraction and further screening, we found 18 studies containing sufficient non-overlapping outcome data suitable for meta-analysis. 24 27 30 31 32 33 34 36 42 48 50 52 61 62 64 66 67 68 Figure 1 shows a PRISMA flow diagram detailing the process of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…In all cases, where respective comparisons were available, studies reported living donor transplantation as conferring a greater survival benefit over deceased donor transplantation, 31 35 45 49 55 59 60 61 63 standard criteria donors over extended criteria donors, 41 47 55 60 69 and finally hepatitis C virus seronegative over hepatitis C virus seropositive donor transplantation. 37 65 Detailed outcome data with adjusted hazard ratios for each study and stratum are provided in supplementary table D. Benefit was found in all adults aged ≥18, older adults (≥60, 24 28 29 38 47 66 67 ≥65, 28 55 58 61 and ≥70 45 50 62 ), and population groups with obesity (body mass index ≥30), 35 diabetes as a comorbidity, 43 44 58 systemic sclerosis, 39 peripheral arterial disease, 43 60 and patients seropositive for hepatitis C virus. 65 …”
Section: Resultsmentioning
confidence: 99%
“…However, with elderly patients, the risk-benefit ratio should be carefully discussed. 12,28 This implies an additional procedure to identify risk factors such as silent cancer, cardiovascular disease, or infection. This preregistration assessment may take time.…”
Section: Discussionmentioning
confidence: 99%
“…According to French guidelines, up to the age of 85, age alone should not be a barrier to waitlisting. However, with elderly patients, the risk‐benefit ratio should be carefully discussed 12,28 . This implies an additional procedure to identify risk factors such as silent cancer, cardiovascular disease, or infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that KT provides superior life expectancy [61][62][63] and QoL [64][65][66] than dialysis. Nonetheless, returning to dialysis after a failed transplant entails a greater risk of death than starting RRT for the first time [11,40,43,67,68].…”
Section: Post-transplant Recipient and Allograft Survivalsmentioning
confidence: 99%